Timing Is Important: Unmanned Aircraft vs. Satellite Imagery in Plant Invasion Monitoring - Müllerová, Jana; Brůna, Josef; Bartaloš, Tomáš; Dvořák, Petr; Vítková, Michaela; Pyšek, Petr (Frontiers in Plant Science, 2017)
The rapid spread of invasive plants makes their management increasingly difficult. Remote sensing offers a means of fast and efficient monitoring, but still the optimal methodologies remain to be defined. The seasonal dynamics and spectral characteristics of the target invasive species are important, since, at certain time of the vegetation season (e.g. at flowering or senescing), plants are often more distinct (or more visible beneath the canopy). Our aim was to establish fast, repeatable and a cost-efficient, computer-assisted method applicable over larger areas, to reduce the costs of extensive field campaigns. To achieve this goal, we examined how the timing of monitoring affects the detection of noxious plant invaders in Central Europe, using two model herbaceous species with markedly different phenological, structural and spectral characteristics. They are giant hogweed (Heracleum mantegazzianum), a species with very distinct flowering phase, and the less distinct knotweeds (Fallopia japonica, F. sachalinensis and their hybrid F. ×bohemica). The variety of data generated, such as imagery from purposely-designed, unmanned aircraft vehicle (UAV) and VHR satellite, and aerial colour orthophotos enabled us to assess the effects of spectral, spatial and temporal resolution (i.e., the target species’ phenological state) for successful recognition. The demands for both spatial and spectral resolution depended largely on the target plant species. In the case that a species was sampled at the most distinct phenological phase, high accuracy was achieved even with lower spectral resolution of our low-cost UAV. This demonstrates that proper timing can to some extent compensate for the lower spectral resolution. The results of our study could serve as a basis for identifying priorities for management, targeted at localities with the greatest risk of invasive species’ spread and, once eradicated, to monitor over time any return. The best mapping strategy should reflect morphological and structural features of the target plant and choose appropriate spatial, spectral and temporal resolution. The UAV enables flexible data acquisition for required time periods at low cost and is, therefore, well suited for targeted monitoring; while satellite imagery provides the best solution for larger areas. Nonetheless, users must be aware of their limits.